2021
DOI: 10.1186/s12889-021-10670-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating role of resources in the temporal relationship between proactive burnout prevention and burnout

Abstract: Background Employees who engage in proactive burnout prevention can prevent burnout by changing aspects of the work, home, and personal domain. However, these proactive behaviors may be impeded by high initial levels of burnout. Based on the conservation of resources theory and the dual-pathway proactivity model, resources were expected to play a vital role in the relationship between proactive burnout prevention and burnout through two distinct processes: a resource-generation process in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
17
0
4
Order By: Relevance
“…Dispositional factors are also related, with workaholism positively related to burnout (Sakakibara et al , 2020), as is perfectionism concerns (Spangnoli et al , 2021). Otto et al (2021a, b) found towards burnout, that self-efficacy and optimism were negatively related. Hence, the job burnout constructs operates as we would expect.…”
Section: Introductionmentioning
confidence: 94%
“…Dispositional factors are also related, with workaholism positively related to burnout (Sakakibara et al , 2020), as is perfectionism concerns (Spangnoli et al , 2021). Otto et al (2021a, b) found towards burnout, that self-efficacy and optimism were negatively related. Hence, the job burnout constructs operates as we would expect.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, several causes are positively related to burnout, including various job demands and workaholism (Sakakibara et al, 2020), job insecurity (Nellestijn, 2019), and perfectionism concerns (Spangnoli et al, 2021). Recent work (Otto et al, 2021a(Otto et al, , 2021b has shown proactive burnout prevention, self-efficacy, and optimism were negatively related to burnout. Finally, De Beer et al ( 2020) investigated the measurement invariance of the BAT using seven different cross-national representative samples, including the Netherlands, Belgium, Austria, Ireland, Finland, and Japan.…”
Section: Bat Supporting Evidencementioning
confidence: 99%
“…Specifically, removing themselves from their job to escape the resource loss condition. Indeed, the COR theory has become a central theoretical approach to studying burnout (Moin et al, 2020), including using the BAT (see Otto et al, 2021; Urbanaviciute et al, 2021).…”
Section: The Present Studymentioning
confidence: 99%